Median nerve stimulation elevates ventricular fibrillation threshold via the cholinergic anti-inflammatory pathway in myocardial infarction canine model - Wang, Xuewen; Qian, Yongsheng; Yao, Yajun; Wang, Youcheng; Zhang, Youjing; Zhang, Shujuan; Zhao, Qingyan (Frontiers in Cardiovascular Medicine, 2022)
Background: Median nerve stimulation (MNS) diminishes regional myocardial ischemia and ventricular arrhythmia; however, the underlying mechanism has not been elucidated. Methods: Herein, we randomly categorized 22 adult mongrel dogs into the control group, MNS group 1, and MNS group 2. After a 4-week experimental myocardial infarction (MI), ventricular electrophysiology was measured in the MNS group 1 dogs before and after MNS 30 min. The same measurements were performed in the MNS group 2 dogs via bilateral vagotomy. Results: No significant changes were reported in the ventricular effective refractory period in the MNS group 1 and MNS group 2 dogs before and after MNS. The ventricular fibrillation threshold (VFT) in the MNS group 1 was significantly higher than that in the MNS group 2 (20.3±3.7 V vs 8.7±2.9 V, P < 0.01). Tumor necrosis levels of factor-alpha and interleukin-6 were lower (P < 0.01), whereas the levels of Ach and NF-κB were higher in the peri-infarct zone tissues in the MNS group 1 dogs than in the MNS group 2 dogs (P < 0.01). Conclusions: This work demonstrated that median nerve stimulation increases VFT in a canine model with MI. The effects of MNS on VFT are potentially associated with the cholinergic anti-inflammatory pathway. Keywords: Myocardial infarction, median nerve, sudden cardiac death, cholinergic anti-inflammatory pathway